2012
DOI: 10.3389/fphys.2012.00417
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in fractal time series analysis: fMRI BOLD as an exemplary case

Abstract: This article will be positioned on our previous work demonstrating the importance of adhering to a carefully selected set of criteria when choosing the suitable method from those available ensuring its adequate performance when applied to real temporal signals, such as fMRI BOLD, to evaluate one important facet of their behavior, fractality. Earlier, we have reviewed on a range of monofractal tools and evaluated their performance. Given the advance in the fractal field, in this article we will discuss the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 116 publications
0
80
0
Order By: Relevance
“…Rodent fMRI-BOLD imaging data of limited definition (Eke et al, 2012) was chosen to demonstrate the performance of our SFD method on scans of bimodal BOLD time series data obtained across a section at the level of the bregma (Herman et al, 2011; Figure 9A). Criteria of 0.5 < H [ f X i ](2) < 2, s x within the full available SR, and 0.1 < s b / s x < 10 yielded valid estimates of crossovers with MSE:SFD-FMF < MSE:qSRA-FMF at a rate of 68%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent fMRI-BOLD imaging data of limited definition (Eke et al, 2012) was chosen to demonstrate the performance of our SFD method on scans of bimodal BOLD time series data obtained across a section at the level of the bregma (Herman et al, 2011; Figure 9A). Criteria of 0.5 < H [ f X i ](2) < 2, s x within the full available SR, and 0.1 < s b / s x < 10 yielded valid estimates of crossovers with MSE:SFD-FMF < MSE:qSRA-FMF at a rate of 68%.…”
Section: Resultsmentioning
confidence: 99%
“…These endpoints are h max [the Hölder exponent, h , at the peak of D ( h )] and fwhm [the full width of D ( h ) at half maximum] (Eke et al, 2012). h max captures the degree of correlation, and fwhm can be taken as the measure of the supporting base of the singularity spectrum (see Figure 3 of Mukli et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Fractional Gaussian noise also mimics typical shape expected from long range correlations and hence can lead to erroneous results (Eke et al, 2012; Delignières and Marmelat, 2013). Bashan et al (2008) have observed that MFDFA1 systematically overestimates the scale scaling exponents for small scale s. In this respect Centered Moving Average (CMA) (Alvarez-Ramirez et al, 2005) will be more fruitful in analyzing the scaling properties in short data sets without trends.…”
Section: Discussionmentioning
confidence: 99%
“…33,[35][36][37] This means the Hurst coefficient must remain constant across all q-order statistical moments. 35,37 More simply, the signal must be simple enough to be described by one fractal dimension. When the selfsimilarity of a time series changes with spatial and temporal variations, the signal is deemed to be multifractal.…”
Section: -Is the Signal Monofractal Or Multifractal?mentioning
confidence: 99%